UJI AKTIVITAS ANALGESIK ASAM 2-(3-(KLOROMETIL)BENZOILOKSI)BENZOAT DAN ASAM 2-(4-(KLOROMETIL)BENZOILOKSI)BENZOAT PADA TIKUS WISTAR JANTAN DENGAN METODE PLANTAR TEST - Wahyu Dewi Tamayanti; Ratna Megawati Widharna; Caroline Caroline; Bambang Soekarjo (Sanata Dharma University, 2016)
The new compounds of salicylic acid derivatives, 2- (3- (chloromethyl) benzoyloxy) benzoic acid and 2- (4- (chloromethyl) benzoyloxy) benzoic acid were synthesized to generate better analgesic activity and lesser stomach irritation of salicylic acid. The 2- (4- (chloromethyl) benzoyloxy) benzoic acid and 2- (3- (chloromethyl) benzoiloksi) benzoic acid were synthesized by Schotten-Baumann acylation process. In this study, analgesic activity was tested by plantar test method. The compounds were administered to the tested animals at 12.5; 25; 50; 100; and 200 mg / kg BW of doses. Analgesic activity was determined by the response time of rat to pain induced by infra red. The percentage of pain hindrance was calculated from the mean of response time to pain. Pain hindrance percentage were shown as: 74.28%; 105.58%; 110.58%; 115.29%; and 175.87% after administration of 2- (4- (chloromethyl) benzoyloxy) benzoic acid at doses of 12.5; 25; 50; 100; and 200 mg / kg. The pain hindrance percentage after administration of 2- (3- (chloromethyl) benzoyloxy) benzoaic acid, were 85.30%; 92.48%; 124.96%; 180.36%; and 208.01% respective to the doses of 12.5; 25; 50; 100; and 200 mg / kg. Five doses of acetyl salicylic acid ranged from 12.5 mg / kg to 200 mg / kg showed pain hindrance percentage as: 26%; 34.34%; 45.68%; 60.38%; and 114.12%. This study indicated that 2- (3- (chloromethyl) benzoyloxy) benzoic acid and 2- (4- (chloromethyl) benzoyloxy) benzoic acid generated higher analgesic activity than acetyl salicylic acid.